Plasma microglial-derived extracellular vesicles are increased in frail patients with Mild Cognitive Impairment and exert a neurotoxic effect - C. Visconte; M.T. Golia; C. Fenoglio; M. Serpente; M. Gabrielli; M. Arcaro; F. Sorrentino; M. Busnelli; A. Arighi; G. Fumagalli; E. Rotondo; P. Rossi; et al. (GeroScience, 2023)
Extracellular vesicles (EVs) are mediators of cellular communication that can be released by almost all cell types in both physiological and pathological conditions and are present in most biological fluids. Such characteristics make them attractive in the research of biomarkers for age-related pathological conditions. Based on this, the aim of the present study was to examine the changes in EV concentration and size in the context of frailty, a geriatric syndrome associated with a progressive physical and cognitive decline. Specifically, total EVs and neural and microglial-derived EVs (NDVs and MDVs respectively) were investigated in plasma of frail and non-frail controls (CTRL), mild cognitive impairment (MCI) subjects, and in Alzheimer’s disease (AD) patients. Results provided evidence that AD patients displayed diminished NDV concentration (3.61 × 10 9 ± 1.92 × 10 9 vs 7.16 × 10 9 ± 4.3 × 10 9 particles/ml) and showed high diagnostic performance. They are able to discriminate between AD and CTRL with an area under the curve of 0.80, a sensitivity of 78.95% and a specificity of 85.7%, considering the cut-off of 5.27 × 10 9 particles/ml. Importantly, we also found that MDV concentration was increased in frail MCI patients compared to CTRL (5.89 × 10 9 ± 3.98 × 10 9 vs 3.16 × 10 9 ± 3.04 × 10 9 particles/ml, P < 0.05) and showed high neurotoxic effect on neurons. MDV concentration discriminate frail MCI vs non-frail CTRL (AUC = 0.76) with a sensitivity of 80% and a specificity of 70%, considering the cut-off of 2.69 × 10 9 particles/ml. Altogether, these results demonstrated an alteration in NDV and MDV release during cognitive decline, providing important insight into the role of EVs in frailty status.